An innovative technical support system for sustainable construction indicators in Zimbabwe - Moyo, Tirivavi; Omer, Mazen Mohamed Alkhdar; Edwards, David J. (Emerald Publishing Limited, 2024)
Purpose – Achieving sustainable construction is immensely challenging in developing economies due to their inadequate technical support system(s) (TSS). Hence, this article develops a TSS framework for sustainable construction indicators for Zimbabwe, a developing country. Design/methodology/approach – A post-positivist philosophicalstance and deductive reasoning were adopted to test pertinent theory. Construction professionals in consultancy, construction companies, government bodies and academic institutions participated in an online questionnaire survey. Primary data was analysed using a reliability test, Shapiro Wilks test, Kruskal–Wallis H test, mean score ranking, normalisation value, factor analysis and fuzzy synthetic evaluation (FSE). Findings – FSE revealed a framework with six critical technical support subgroups, in order of importance viz: innovation for construction sustainability; adequate sustainability expenditure and skills training support; adequate project economic assessment and governance support; adequate circularity and environmental technical support; climate change literacy and supplier assessment support; and adequate decent work support. Existing sustainable construction initiatives can be buttressed by strengthening the six identified TSS through related policy initiatives. Originality/value – The framework developed constitutes an innovative TSS for Zimbabwe to achieve sustainable construction.